The divisibility of the soul in the Aristotle´s Psychology. Is it possible to reconcile the Hylomorphism and the Cardiocentrism? - Mora Alonso, César Augusto (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2018)
The purpose of this paper is to highlight the central role of the problem of divisibility of the soul in the two approaches under which the Aristotelian psychological research is presented: hylomorphism and cardiocentrism. While the first states that the soul is the form or essence of the whole body, the second advocates the location of the soul in the heart, because affirms that there are the principles of the parts of the soul. This could lead to assume that there is an incompatibility between the two approaches, since it would make no sense to say that the soul is in the whole body and, at the same time, declare that is found exclusively in one of its specific organs. For this reason, the thesis of this paper is that the pneuma provides the key to reconciling the two approaches, inasmuch as it is the instrument used by the parts of the soul to deploy its functions throughout the body. The heart, as a material seat of this parts, spreads the pneuma as blood throughout the body; and this, until no ends this vital function, preserves its essence, raison d’etre of its existence. Thus hylomorphism is supported by cardiocentrism.
Keywords: Soul; parts of the soul; heart; hylomorphism; cardiocentrism.